Factor Content of Bilateral Trade: The Role of Firm Heterogeneity and Transaction Costs - D'Artis Kancs; Pavel Ciaian (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
In this paper we study the detfirminants of the factor content of the CEE agricultural trade. Examining empirically three hypothesis, which relate cross-country differences in technology, relative factor abundance and transaction costs and market imperfections to the factor content of trade we find that the first two hypotheses are confirmed by the majority of developed EU countries, but rejected by roughly one half of the CEE transition country pairs. Second, we find that when accounting for transaction costs of firm (re)organization, both hypotheses are confirmed by the majority of the CEE country pairs. These findings provide empirical evidence of market imperfections, and particularly, of transaction costs of firm (re)organization in the CEE.
Keywords: F12; F14; D23; Q12; Q17; 330; Factor content; bilateral trade; relative factor abundance; technological differences; agriculture; transaction costs; Agraraußenhandel; Faktorproportionentheorem; Faktorintensität; Transaktionskosten; Unvollkommener Markt; Osteuropa